Penerapan Metode MOORA Pada Sistem Pendukung Keputusan Penilaian Kinerja Program Studi - Sri Poedji Lestari; Bernadus Gunawan Sudarsono (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The Head of the Study Program is fully responsible for the process of academic sustainability activities in the study program he leads. In addition to being responsible for managerial functions, the Head of the Study Program is also responsible for whether or not the study program he leads is active or not. In addition, the Head of the Study Program must also be able to protect his subordinate members who are structurally in the study program. Therefore, the Head of the Study Program must be required to have high integrity and competence. So in this case, it is necessary to evaluate the performance of the highest leadership at the university. The performance assessment is carried out to assess whether the Head of the Study Program is still eligible to serve again for that position or not. So in this case the assessment must be carried out as well as possible and also as objectively as possible so that the results of the assessment carried out do not harm one party and can also be held accountable. Decision Support System is a system that is part of an information system that is able to process data and is used for organizations in helping managerial parties to solve semi-structured problems. The Multi-Objective Optimization method on the basis of ratio Analysis (MOORA) is a multi-objective method of optimizing two or more conflicting attributes simultaneously. The results obtained in research using Decision Support Systems get objective, optimal and also good results. The highest Head of Study Programs in a row are alternatives A2, A6, A5 and A4. As for the Head of the Study Program, the lowest ratings from the bottom are A1 and A3 respectively.